(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article is focused on the principles of creating a perfect “Baburname” corpus. Gathering the achievements in Babur studies, defining the problems, showing its role in the development of world culture, the growing interest in Babur’s personality, activities, and creativity on a global scale, and the emergence of new researches in Babur studies require the creation of this corpus. The facts that creating an electronic database on Babur’s life and activities, processing texts on the basis of artificial intelligence; compiling a corpus of parallel texts related to the translations of “Baburname”, conducting a search based on various symbols, explaining the social-political, cultural-educational features of the “Baburname” text; the importance of studying the translations, researches accomplished on Uzbek, Turkish, Azerbaijani, Kazakh, Kyrgyz, Russian, English, German, French languages were all the basis for creating “Baburname” corpus were analyzed.